Utilization of Immediate Postpartum Long Acting Reversible Contraceptives among Women Who Gave Birth in Public Health Facilities in Eastern Ethiopia: A Cross-Sectional Study - Usso, Ahmedin Aliyi; Adem, Hassen Abdi; Dessie, Yadeta; Tura, Abera Kenay (International Journal of Reproductive Medicine, 2021)
Objective. Although importance of postpartum family planning is essential and immediate postpartum insertion of long acting and reversible contraceptives (LARC) is recommended, evidence on its uptake and associated factors is limited in Ethiopia. This study was conducted to assess utilization of immediate postpartum LARC among women who gave birth in selected public health facilities in eastern Ethiopia. Method. An institution-based cross-sectional study was conducted among randomly selected women who gave birth in selected public health facilities in eastern Ethiopia from 10 March to 09 April 2020. At discharge, all eligible women who gave birth in the facilities were interviewed using a pretested structured questionnaire. Data were entered using EpiData 3.1 and analyzed using SPSS 24. Bivariable and multivariable logistic regression analyses were conducted to identify factors associated with utilization of immediate postpartum LARC. Adjusted odds ratio (aOR) with 95% confidence interval was used to report association, and significance was declared at p value < 0.05. Results. From a total of 546 women invited to the study, 530 (97.1%) participated in the study and 98 (18.5%; 95% CI: 15.1%, 22.0%) reported starting long acting reversible contraceptives. Women who reported discussing about contraceptives with partners (aOR=6.69, 95% CI: 3.54, 12.61) and receiving postpartum counselling on contraceptives (aOR=5.37, 95% CI: 3.00, 9.63) were more likely to using contraception. However, women who live >30-minute walking distance from the nearest health facility (aOR=0.47, 95% CI: 0.26, 0.85) and reported disrespect and abuse during childbirth (aOR=0.22, 95% CI: 0.12, 0.40) were less likely to start LARC. Conclusions. Almost one in five women delivering in public health facilities in eastern Ethiopia started using LARC. Provision of respectful maternity care including counselling on the importance of immediate postpartum family planning is essential for increasing its uptake.